1997
DOI: 10.1136/thx.52.1.49
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of adults with asthma: a prospective cohort study

Abstract: Some of the inconsistency may have arisen from confounding since, although many studies Background -Few studies have been published on the overall survival of adult have controlled for the effect of age, sex and smoking, 2 5 15 the effects of occupation 15 and patients with asthma. A cohort study was performed to assess the mortality from all other lung diseases 2 may also be important. We have studied mortality from all causes among causes, from chronic obstructive pulmonary disease, and from lung cancer pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
63
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 17 publications
8
63
1
Order By: Relevance
“…They also stressed the role of an FEV1 ofv80% pred as a predictor of mortality, but its role was similar in asthmatics and nonasthmatics. The mortality rate from all causes in the present study is comparable to those reported in previous studies; MARKOWE et al [8] found increased mortality from all causes (RR 1.6, 95% CI 1.3-2.0) and HUOVINEN et al [30] found an age-adjusted RR of 1.5 (95% CI 1.1-2.1).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…They also stressed the role of an FEV1 ofv80% pred as a predictor of mortality, but its role was similar in asthmatics and nonasthmatics. The mortality rate from all causes in the present study is comparable to those reported in previous studies; MARKOWE et al [8] found increased mortality from all causes (RR 1.6, 95% CI 1.3-2.0) and HUOVINEN et al [30] found an age-adjusted RR of 1.5 (95% CI 1.1-2.1).…”
Section: Discussionsupporting
confidence: 81%
“…This finding supports the hypotheses of previous studies, according to which asthma is a risk factor for COPD and COPD a risk factor for mortality in asthma [29]. No significant excess in mortality from lung cancer was found among asthmatics, unlike in the studies of BOFFETTA et al [6], HUOVINEN et al [30] and WU et al [31], in which the risk of death due to lung cancer adjusted for smoking was higher in males with asthma (RR 3.2, 95% CI 1.4-7.3). However, no long-term survival studies controlled for occupational exposure.…”
Section: Discussioncontrasting
confidence: 54%
“…The increased risk for lung cancer was noted in many earlier studies (Vesterinen et al, 1993;Huovinen et al, 1997;Mayne et al, 1999;Boffett et al, 2002). Smoking is a common risk factor for lung cancer and asthma (Silverman et al, 2003;Eisner, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that inflammatory lung diseases, including asthma and chronic bronchitis are associated with increased incidence of lung cancer (Alavanja et al, 1992;Kallen et al, 1993;Vesterinen et al, 1993;Wu et al, 1995;Huovinen et al, 1997;Mayne et al, 1999;Brownson and Alavanja, 2000;Brenner et al, 2001).…”
Section: Epidemiologymentioning
confidence: 99%